PEMBELAJARAN MATEMATIKA BERBANTUAN KOMPUTER DI SEKOLAH DASAR - Hidayati, Kurnia (IAIN Ponorogo, 2011)
The use of any methods and media in the learning process has both advantages and disadvantages. Similarly, the teaching of math assisted by computer might be beneficial or give less impact to the studentsâ learning progress. No matter how great the technology used, but if the existing human resources are not yet ready to use it, then the results obtained must not be satisfying. For this reason, it is recommended that teachers should always enhance their capabilities, especially in the field of technology and information, so as to be able to help students actively involve in productive learning process and gain the learning objectives. In line with this case, the math teachers in elementary school are expected to be more creative and innovative in delivering the materials, so students do not experience boredom and able to understand all the material presented well. Some benefits gained from the computer as a learning tool are such as: (1) facilitating the students and teachers in the in learning process, (2) providing the students with some programs, i.e. producing graphics, images and provide a variety of information, (3) helping teachers in the classroom since it is very flexible and can be adjusted according to the curriculum, and (4) assessing each student with immediate results. ÙØ§Ù Ø§ÙØªØ¯Ø±ÙØ³ Ø¨Ø£ÙÙ Ù Ø¯Ø®Ù ÙØ£ÙØ©Ù Ø·Ø±ÙÙØ© ÙÙÙ Ø§ Ù Ø²Ø§ÙØ§ ÙØ¹ÙÙØ¨. ÙÙÙØ°Ø§ Ø§ÙØªØ¯Ø±ÙØ³ Ø¨Ø¬ÙØ§Ø² Ø§ÙØØ§Ø³ÙØ¨Ø Ø¥Ø°Ø§ ÙØ§Ù Ø§ÙÙ ÙØ±Ø¯ Ø§ÙØ¨Ø´Ø±ÙÙ ØºÙØ± Ù Ø³ØªØ¹Ø¯Ù ÙØ§Ø³ØªØ®Ø¯Ø§Ù Ø£ØØ³Ù Ø£ÙÙØ§Ø¹ Ø§ÙØªÙÙÙÙÙØ¬ÙØ§ ÙÙÙ ÙØ§ ÙÙÙØ¹ ÙØ«ÙØ±Ø§. ÙÙÙØ°Ø§Ø Ø¹ÙÙ Ø¬Ù ÙØ¹ Ø§ÙÙ Ø¯Ø±ÙØ³ÙÙ Ø£Ù ÙØ±ÙÙÙØ§ ÙØ¯Ø±Ø§ØªÙÙ ÙÙ Ù Ø¬Ø§Ù ØªÙÙÙÙÙØ¬ÙØ© Ø§ÙØ£Ø®Ø¨Ø§Ø± ÙÙÙØ¯Ø±ÙØ§ Ø¹ÙÙ Ø¥Ø´Ø±Ø§Ù ØªÙØ§Ù ÙØ°Ù Ø¨ÙØ¬Ù Ø§ÙÙ Ù ÙÙØ§ Ø³ÙÙ Ø§ Ù Ø¯Ø±Ø³ÙØ§ Ø¹ÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¦ÙØ© ÙÙÙÙÙÙØ§ Ù Ø¬Ø¯ÙØ¯ÙÙ ÙÙ Ø¨Ø¯Ø¹ÙÙ ÙÙ ØªÙØ¯ÙÙ Ø§ÙÙ ÙØ§Ø¯ ÙØ§Ø²Ø§ÙØ© Ø³Ø¢Ù Ø© Ø§ÙØ·ÙØ§Ø¨ ÙÙ Ø§ÙØ¯Ø±Ø§Ø³Ø© ØØªÙ ÙÙÙÙ ÙØ§ Ø§ÙØ¯Ø±Ø³ Ø¬ÙØ¯Ø§. ÙØ«Ù Ø© Ù ÙØ§ÙØ¹ ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØØ§Ø³ÙØ¨ ÙÙØ³ÙÙØ© ÙÙØªØ¯Ø±ÙØ³ (1) ÙØ³Ø§Ø¹Ø¯ Ø§ÙØØ§Ø³ÙØ¨ Ø§ÙÙ Ø¯Ø±Ø³ ÙØ§ÙØ¯Ø§Ø±Ø³ÙÙ ÙØ«ÙØ±Ø§ (2) ÙÙ ÙØ¯Ø±Ø§Øª ÙØ«ÙØ±Ø© Ù Ù ØªØ§Ø²Ø© ÙÙ Ø§ÙØØ³Ø§Ø¨ ÙØªÙÙÙÙ Ø§ÙØµÙØ± Ù ØªÙØ¯ÙÙ Ø§ÙÙ Ø¹ÙÙÙ Ø§Øª Ø§ÙÙ ØªÙÙØ¹Ø©Â (3) ÙÙ ÙÙ Ø§Ø³ØªØ¹Ù Ø§ÙÙ Ø¨Ø³ÙÙÙØ© Ø¹ÙÙ ØØ³Ø¨ Ù Ø³ØªØ®Ø¯Ù ÙÙ (4) ÙØ¯Ø±ØªÙ Ø¹ÙÙ ØªÙÙÙÙ ÙÙ Ø·Ø§ÙØ¨ Ø¨Ø³Ø±Ø¹Ø© .